The Behavior of the Type of Peritoneal Transport in the Inflammatory and Oxidative Status in Adults Under Peritoneal Dialysis - Gutiérrez-Prieto, Julio Alejandro; Soto-Vargas, Javier; Parra-Michel, Renato; Pazarín-Villaseñor, Héctor Leonardo; García-Sánchez, Andrés; Miranda-Díaz, Alejandra Guillermina (Frontiers in Medicine, 2019)
Peritoneal dialysis (PD) is a renal replacement therapy for the management of end-stage renal disease (ESRD). The peritoneal membrane (PM) is not just a membrane that passively responds to diffusion and convection; the characteristics of PM result in the peritoneal equilibrium test (PET) and with this test is possible to obtain the type of peritoneal transport (PT). The patient on PD can be classified in different types of PT as; Low, Low Average, High Average and High. The aim of the study was to compare the levels of pro-inflammatory cytokines, oxidants, antioxidants, and oxidative DNA damage markers in the different types of PT. Through an analytical cross-sectional study in 77 adult in PD patients was performed. Levels of lipoperoxides (LPO) were significantly higher in all types of PT compared to healthy controls (HC) (p<0.0001). Nitric oxide (NO) levels were found significantly down-regulation in all types of PT (p<0.0001). The activity of the superoxide dismutase (SOD) enzime was found to be significantly increased in all types of PT vs. the HC (p<0.0001). The levels of the DNA repair enzyme were found to be decreased (NS) in all types of PT. The levels of the pro-inflammatory cytokines TNF-α, IL-6, the marker of oxidative DNA damage, 8-IP and the total antioxidant capacity (TAC) they were all significantly decreased, contrary to the levels in HC, possibly by the clearance in the dialysis fluid in all types of PT or due to a down-regulation of their expression. In conclusion, we found an imbalance in the state of inflammation and oxidative stress in all types of PT. The important decrease in NO could suggest the disturbance in the endothelial bioavailability that could indicate endothelial dysfunction. Inactivity or down-regulation of the DNA repair enzyme and increased activity of the systemic SOD enzyme suggests compensatory effect in view of the increase in oxidative stress.